Integration of technology in differentiated learning to improve student learning outcomes in elementary school - Anggraini, Diah Retno; Yahrif, Muhamad; Deani, Amira (Arshaka: Social Sciences and Education, 2025)
This study aims to measure the impact of technology integration in differentiated learning on student learning outcomes in elementary school. Using a quantitative experimental design with a pre-test post-test approach, this study involved 120 students of School 231 Sukaasih who were divided into two groups: an experimental group that used technology in differentiated learning and a control group that used traditional methods. Data was collected through pre-test, post-test, and student engagement questionnaires. Data analysis was conducted using t-tests for group comparison and linear regression to analyze the relationship between student engagement and learning outcomes. The results showed that the experimental group experienced a significant improvement in learning outcomes, with a higher average post-test score than the control group. In addition, higher student engagement in technology-based learning was positively associated with improved learning outcomes. These findings indicate that the use of technology in differentiated learning can improve students' understanding of the material and increase their engagement in the learning process. The implication of this study is the importance of integrating technology in education to improve the quality of learning, but this requires infrastructure support and training for teachers to maximize its benefits.